Crisis Management Policies Concerning the Russo- Ukrainian War in the European Union’s Security and Defence Approach: Soft Power and EUAM - Aydemir, Emrah; Güner, Oguz (My University, 2023)
The European Union (EU) has long been formulating security and defense policies, and strategy documents, incorporating modern developments, based on joint assessment of threats and challenges against the security of Europe. European Union, while striving to optimize existing sources and boosting the overall efficiency of crisis management policies to address foreign crises, falls short of substantial progress in overcoming the challenges. This article aims to discuss the EU’s crisis management policies regarding the Russo-Ukrainian War, covering the years 2014-2022, from a historical perspective on the Union’s approach to security and defense. In this context, this article focuses on the use of soft power and European Union Advisory Mission (EUAM) adopted by the European Union for Ukraine as part of its crisis management policy, and evaluates the security and defense approach it has displayed in resolving the crisis combined with the objectives pursued and the goals to be achieved.
Keywords: European Union; Russia; Ukraine; soft power; EUAM; crisis management policies